Eksplorasi Ketimpangan dan Klasterisasi Pembangunan Manusia di Provinsi Nusa Tenggara Timur - Dwi Rizky Syaifullah; Diah Mekita Sari (Jurnal Statistika Terapan (ISSN 2807-6214), 2025)
The Human Development Index (HDI) is a crucial metric for assessing multidimensional regional development quality. Nusa Tenggara Timur Province (NTT) has one of the lowest HDI scores in Indonesia, reflecting persistent challenges in education, health, and economic conditions. This study examines HDI disparities in NTT and classifies its regencies/municipality using Coefficient Variation (CV) and K-means clustering. CV quantifies inequality among regencies/municipality, while K-means clustering segments regions based on HDI patterns. The novelty of this study lies in integrating CV analysis with K-means clustering, providing a more comprehensive approach to understanding HDI disparities. This combined method allows for a more detailed classification of regions, offering insights for more targeted policy interventions. The findings reveal a decline in HDI disparity from 2020 to 2024, primarily driven by improvements in the living standard dimension. However, significant gaps persist, particularly in education and health accessibility. The clustering analysis identifies four distinct regional groups: (1) "Healthy and Educated Regions" with high life expectancy and schooling rates, (2) "Underdeveloped Regions" with low scores across all HDI components, (3) "Educated Regions" with strong educational indicators but weaker health and income levels, and (4) "Developed Regions" exhibiting high scores across all HDI dimensions. Addressing disparities in the living standard dimension remains a key strategy for fostering equitable human development in NTT.